IMPLICATION OF PROTECTION AND FULFILLMENT OF WOMEN'S POLITICAL RIGHTS THROUGH AFFIRMATIVE ACTION POLICY - Asikin, Nur (Faculty of Law, Pattimura University, 2017)
One group of citizens who because of the conditions require special treatment is women. Without special treatment or affirmative action, women will not be able to access the protection and fulfillment of their constitutional rights because of the differences and distinctions generated and perpetuated by the structure of patriarchal society. The protection and fulfillment of constitutional rights without special treatment will tend to maintain discrimination against women and unable to achieve justice